2020
DOI: 10.1101/2020.07.10.197186
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved Accuracy for Modeling PROTAC-Mediated Ternary Complex Formation and Targeted Protein Degradation via NewIn SilicoMethodologies

Abstract: Extending upon our previous publication (Drummond and Williams, J. Chem. Inf. Model.2019, 59, 1634), in this work two additional computational methods are presented to model PROTAC-mediated ternary complex structures, which are then used to predict the efficacy of any accompanying protein degradation. Method 4B, an extension to one of our previous approaches, incorporates a clustering procedure uniquely suited for considering … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…Ternary complex formation is thought to be the most important factor in determining the degradability of protein targets 53,[55][56][57][58][59] . However, our analysis found that protein degradability can also be heavily influenced by protein-intrinsic features, especially the protein's endogenous ubiquitination potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ternary complex formation is thought to be the most important factor in determining the degradability of protein targets 53,[55][56][57][58][59] . However, our analysis found that protein degradability can also be heavily influenced by protein-intrinsic features, especially the protein's endogenous ubiquitination potential.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely believed that stable ternary complexes are associated with effective and selective target degradation 15,16,53,55 . A series of computational methods have been introduced to model PROTAC-mediated ternary complex formation [56][57][58][59] , which have facilitated the rational and efficient optimization of PROTACs 16,60 . However, several studies have shown that although some level of binary target engagement and ternary complex formation are necessary for target recruitment and ubiquitin transfer, they are not always sufficient for targeted protein degradation [51][52][53]61 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, this work was extended by the addition of clustering to improve its performance. 24 Very recently, a new Rosetta-based protocol was also reported that successfully rationalized PROTAC structure–activity relationships. 25 Some system specific modeling efforts were also reported.…”
Section: Introductionmentioning
confidence: 99%
“…With the most promising method of combining docking of the two protein-ligand structures with separate PROTAC conformer generation, they showed that it is possible to recover near-native ternary complexes for a few available PDBs. In follow-up work [31], Drummond et al added two additional methods which improve the previous performance. This work introduces clustering of the generated structures, an essential step in obtaining good results.…”
Section: Introductionmentioning
confidence: 99%